2020
DOI: 10.1055/s-0040-1713166
|View full text |Cite
|
Sign up to set email alerts
|

CRISPLD2 Gene Polymorphisms with Nonsyndromic Cleft Lip Palate in Indian Population

Abstract: AbstractCleft lip palate (CLP) is one of the common congenital anomalies with multifactorial etiology. Many genes are associated with its etiology. In one of the studies CRISPLD2 gene polymorphisms rs1546124, rs4783099, and rs16974880 were reported in the Chinese population. However, its role in the Indian population is not yet studied. Hence, this research was conducted on the Indian population to know the role of these high-risk polymorphisms in patients with nonsyndromic CLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The family studies for the Indian population reported that several genes such as CRISPLD2, RUNX2, SOX1-OT, MAPK4, CTIF, MYO5B, SMAD7, LOXHD1, and SKA1 are not associated with NSCLP in Indian multiplex families. [15][16][17] However, there are no reported case-parent trio studies of the PAX7 gene in the Indian population. Case-parent trio design studies are generally used in genetics, in which the affected children and their parents (father and mother) are genotyped.…”
Section: Discussionmentioning
confidence: 99%
“…The family studies for the Indian population reported that several genes such as CRISPLD2, RUNX2, SOX1-OT, MAPK4, CTIF, MYO5B, SMAD7, LOXHD1, and SKA1 are not associated with NSCLP in Indian multiplex families. [15][16][17] However, there are no reported case-parent trio studies of the PAX7 gene in the Indian population. Case-parent trio design studies are generally used in genetics, in which the affected children and their parents (father and mother) are genotyped.…”
Section: Discussionmentioning
confidence: 99%
“… 14 They may occur as unilateral or bilateral, complete, or incomplete, and may involve the lip only, the palate only, or both. 15 …”
Section: Epidemiologymentioning
confidence: 99%
“…14 They may occur as unilateral or bilateral, complete, or incomplete, and may involve the lip only, the palate only, or both. 15 The prevalence of OFC varies according to geographical location, ethnicity, race, gender and socioeconomic status, [16][17][18][19] Asians have the highest prevalence rate (1:500), the intermediate prevalence in Europeans (1:1000), and lowest in Africans (1:2500). [20][21][22] In India, the incidence of clefts is around 1:800 to 1:1000, and three infants are born with some type of cleft every hour.…”
mentioning
confidence: 99%
“… 11 Consanguinity is a risk factor for nonsyndromic CL/P in the Indian population, according to a 13-year retrospective study from a cleft center. 12 …”
Section: Introductionmentioning
confidence: 99%
“…11 Consanguinity is a risk factor for nonsyndromic CL/P in the Indian population, according to a 13-year retrospective study from a cleft center. 12 The paired box 7 (PAX7) gene is a member of the paired box (PAX) family, located at 1p36.13, and encodes specific DNA-binding transcription factors. PAX7 is involved in neural crest development, myogenesis, and maxilla development in humans.…”
Section: Introductionmentioning
confidence: 99%